Digital Marketing Strategies applied in Ecuadorian Interprovincial Transport companies - Lindao Palma, Tania Leonela; Carrera Jiménez, Javier; Cueva Estrada, Jorge; Sumba Nacipucha, Nicolás (Revista Minerva, 2023)
The transport sector is essential to support the economic and social development of countries, in addition to being a source of employment, it allows connecting people with essential services, such as education and health. The objective of this research is to analyze the current situation regarding digital marketing applied by Ecuadorian interprovincial transport companies, as well as to propose digital marketing strategies to increase the flow of passengers of companies and interprovincial transport companies that operate in the Ecuador. For this, 15 managers, administrators and leaders of transport operators were interviewed, and a questionnaire was applied to 385 interprovincial transport users. The results indicate that interprovincial transport companies have little positioning in social networks and those that have web pages do not have attractive portals that allow interaction with their users. It is concluded that the reality of the market and the digital marketing of land transport companies that operate in Ecuador, do not have true digital advertising, nor a good use of digital resources, losing opportunities to increase their sales and improve their services.